Multifunctional applications of bamboo crop beyond environmental management: an Indian prospective. Issue 4 (1st April 2022) - Rathour, Rashmi; Kumar, Hemant; Prasad, Komal; Anerao, Prathmesh; Kumar, Manish; Kapley, Atya; Pandey, Ashok; Kumar Awasthi, Mukesh; Singh, Lal
ABSTRACT: Increasing population, industrialization, and economic growth cause several adverse impacts on the existing environment and living being. Therefore, rising pollutants load and their mitigation strategies, as well as achieving energy requirements while reducing reliance on fossil fuels are the key areas, which needs significant consideration for sustainable environment. Since India has considerable biomass resources, bioenergy is a significant part of the country's energy policy. However, the selection of feedstock is a crucial step in bioenergy production that could produce raw material without compromising food reserve along with the sustainable environment. Higher growth capacity of bamboo species makes them a suitable lignocellulosic substrate for the production of high-value greener products such as fuels, chemicals, and biomaterials as well as an appropriate candidate for eco-restoration of degraded land. In that context, the current review discusses the multidimensional applications of bamboo species in India. The bioenergy potency of bamboo and probability of aligning its production, cultivation, and operation with economic and social development agendas are also addressed, making it an exceptional crop in India. Additionally, its fast growth, perennial root systems, and capability to restore degraded land make it an essential part of ecological restoration. Furthermore, this review explores additional benefits of bamboo plantation on the environment, economy, and society along with future research prospects.